Case Report: Spinal Stabilization Surgery Using a Novel Custom-Made Titanium Fixation System for the Spinal Instability Caused by Vertebral Malformation in a Dog - Kimura, Shintaro; Nakata, Kohei; Nakano, Yukiko; Nozue, Yuta; Konno, Naoyuki; Sugawara, Taku; Maeda, Sadatoshi; Kamishina, Hiroaki (Frontiers in Veterinary Science, 2021)
A 2-year-old Maltese was presented with wobbly gait of the pelvic limbs. Based on imaging examinations, a diagnosis of congenital malformation at T5–T8 and severe kyphosis causing spinal cord compression at T6–T7 was made. Dorsal laminectomy and stabilization of T6 and T7 vertebrae were performed. As the size of the vertebrae was small and they were severely deformed, novel custom-made titanium implants were used for spinal stabilization. Clinical signs were resolved 2 weeks after surgery. Although radiographic examination 373 days after surgery showed slight loosening of implants, post-operative course remained uneventful. This report describes the use of novel custom-made titanium implants for spinal fixation surgery in a dog.